Perivascular epithelioid cell tumor of the descending colon mimicking a gastrointestinal stromal tumor: a case report. Issue 1 (December 2016) - Iwamoto, Ryuta; Kataoka, Tatsuki; Furuhata, Ayako; Ono, Kazuo; Hirota, Seiichi; Kawada, Kenji; Sakai, Yoshiharu; Haga, Hironori
Abstract Background We present a case of perivascular epithelioid cell tumor (PEComa), which clinically and histologically mimics a gastrointestinal stromal tumor (GIST). Case presentation A 42-year-old woman was found to have a mass in the left flank during her annual medical checkup. Computed tomography examination revealed a submucosal tumor of the descending colon. Surgeons and radiologists suspected that the lesion was a GIST, and left hemicolectomy was performed without biopsy. Microscopic examination showed that the lesion was composed of spindle and epithelioid cells, which were immunohistochemically negative for c-kit and positive for platelet-derived growth factor receptor (PDGFR) α. Initial diagnosis of PDGFRα-positive GIST was made. However, gene analysis did not reveal mutations in PDGFRα. Additional immunohistochemistry showed that tumor cells were positive for human melanin black 45 (HMB45), melanA, and the myogenic marker calponin. A final diagnosis of PEComa was made. Conclusion PEComa should be included in the differential diagnosis of PDGFRα-positive spindle cell tumors in the wall of the gastrointestinal tract.